Study of troponin-t elevation in critically ill patients-incidence and outcome - Sabu, Augustine; Madhu, S.; Avarebeel, Shilpa; Velangupara, Sruthy; Goudar, Mohan (International Journal of Advances in Medicine, 2017)
Background: Besides cardiac disease, critical illness patients are often subjected to myocardial injury. Hence, the goal of present study was to analyze the incidence of elevated cardiac troponin levels in critically ill patients and its outcome which in turn can act as a prognostic marker. Methods: The settings were the ICU’s of a tertiary care hospital in south India. A sample of 54 was identified using purposive sampling technique. Serial monitoring of troponin T was done on day 1, 3 and 5. A performa was used to collect the baseline data of who met the inclusion and exclusion criteria. The collected data was analyzed by using descriptive and inferential statistics. Results: Among 54 patients 17 (31.5%) of them expired. It was found that patients with mean APACHE score were significantly greater among mortality group (P<0.001). When analyzing the outcome in relation to the troponin T levels, it can be concluded that troponin levels were higher among patients who died but it was not statistically significant. (p=0.56, 0.84 and 0.67 on day 1, 3 and 5 respectively). Among the 54 patients it is inferred from the findings that most of the critically ill patients do have high troponin T levels. Conclusions: The study illustrated the incidence of high troponin T levels in critically ill patients which is an informative prognostic indicator. The relation couldn’t be proved due to less sample size and other imposing factors in critically ill such as broad diagnostic categories.